Teaching English Vocabulary To The Seventh Grade Students Of Smp Muhammadiyah 5 Surakarta - Erfan Nugroho, Muhamad (2015)
This research paper is intended to describe (1) the general objectives of teaching English and the goal of teaching vocabulary (2) the material of teaching vocabulary (3) the technique of teaching English vocabulary (4) procedures in teaching English vocabulary. The type of the research is descriptive qualitative research. The subject of this research is the English teacher and the seventh grade students of SMP Muhammadiyah 5 Surakarta. The data sources of this research are from informant (English teacher, students), document, and event. The techniques of collecting data were observation, interview and document analysis. The researcher uses Miles and Huberman's theory cited in Sugiono (2010:337) in analyzing the data. The researcher after collected the data, the researcher reducing the data, display the data and verifying the data. The findings of this research show that (1) The objective of teaching English is to develop the language skills and communicate written and orally dealing with the development of science and technology and the globalization era, and the objective of teaching vocabulary is to help the students to achieve vocabulary in the material according to the themes. (2) The material given to the students is in the form of text. The materials are taken from English book entitled "Practice Your English Competence" by Erlangga publisher. The teacher also searches another relevant material from internet. (3) The teacher uses "lecturing and observing" technique in teaching vocabulary. (4) the procedure of teaching vocabulary is discuss, show, explain, restate, refine and reflect.